Science and Technology Diplomacy, Volume II: A Focus on the Americas with Lessons for the World - Vafai, Hassan A; Lansey, Kevin E (Momentum Press, 2018)
Science diplomacy and policy can support collaborative national and international science for advancing knowledge with societal impact in fields such as climate, space, medicine, and the environment., Scientific advances made possible by the basic and applied research carried out by government agencies, universities, and nongovernmental organizations create opportunities and challenges with growing impact on policy decisions. Developing structures that produce the best science information to policy makers is becoming more critical in an ever-changing world. This three-volume set presented by prominent figures from the disciplines of science, engineering, technology, and diplomacy includes their perspectives on potential solutions to opportunities 21st-century scientists, engineers, and diplomats face in the future: To shed light and interface science, technology, and engineering with the realm of policy; To provide a vision for the future by identifying obstacles and opportunities while focusing on several key issues.